Measurement of the τ lepton polarization in Z boson decays in proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV - Collaboration, Cms; Hayrapetyan, Aram; Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Bergauer, Thomas; Chatterjee, Suman; Damanakis, Konstantinos; Dragicevic, Marko; Escalante Del Valle, Alberto; Hussain, Priya Sajid; Jeitler, Manfred; et al. (Springer Science and Business Media LLC, 2024)
Abstract The polarization of τ leptons is measured using leptonic and hadronic τ lepton decays in Z → τ + τ − events in proton-proton collisions at $$ \sqrt{s} $$ s = 13 TeV recorded by CMS at the CERN LHC with an integrated luminosity of 36.3 fb −1. The measured τ − lepton polarization at the Z boson mass pole is $$ {\mathcal{P}}_{\tau}\left(\textrm{Z}\right) $$ P τ Z = −0.144 ± 0.006 (stat) ± 0.014 (syst) = −0.144 ± 0.015, in good agreement with the measurement of the τ lepton asymmetry parameter of A τ = 0.1439 ± 0.0043 = $$ -{\mathcal{P}}_{\tau}\left(\textrm{Z}\right) $$ − P τ Z at LEP. The τ lepton polarization depends on the ratio of the vector to axial-vector couplings of the τ leptons in the neutral current expression, and thus on the effective weak mixing angle sin2 $$ {\theta}_{\textrm{W}}^{\textrm{eff}} $$ θ W eff , independently of the Z boson production mechanism. The obtained value sin2 $$ {\theta}_{\textrm{W}}^{\textrm{eff}} $$ θ W eff = 0.2319 ± 0.0008(stat) ± 0.0018(syst) = 0.2319 ± 0.0019 is in good agreement with measurements at e + e − colliders.
Keywords: lepton; GeV-cms; pole; QC770-798; Hadron-Hadron Scattering; Tau Physics; Z0: mass; tau physics; decay; Particle physics; Large hadron collider; CMS; high energy physics; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); lepton, polarization; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; Z0; tau: polarization; info:eu-repo/classification/ddc/530; hadron-hadron scattering; coupling, axial-vector; tau: pair production; CMS; Physics; ddc:530; mass, pole; axial-vector; mass: pole; Weinberg angle; CERN LEP Stor; p p; CERN LHC Coll; Particle physics; LHC; Hadron-Hadron Scattering; Tau Physics; asymmetry; mixing angle: measured; p p: scattering; CERN Lab; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; neutral current; p p, scattering; FOS: Physical sciences; Z0: pole; weinberg angle; polarization: measured; hadron-hadron scattering; Tau physics; lepton; boson; Nuclear and particle physics. Atomic energy. Radioactivity; Z0, mass; TeV; coupling; Z0, decay; experimental particle physics; polarization; Hadron-Hadron Scattering; hep-ex; scattering; Z0: hadroproduction; Large hadron collider; lepton: asymmetry; Tau Physics; coupling: axial-vector; Physics and Astronomy; Hadron-Hadron Scattering; Tau Physics; High-Energy Physics; CMS; CERN; LHC; Z0: leptonic decay; mass; lepton, asymmetry; production; lepton: polarization; Z0, production; p p: colliding beams; lepton, decay; experimental results